The beneficial effects of an adenotonsillectomy upon upper respiratory tract infections, asthma and rhinitis in children: a national database study in Korea. (1st February 2023) - Bae, Mi Rye; Han, Kyung-Do; Park, Sang-Hyun; Chung, Yoo-Sam
Abstract: Background: Adenotonsillectomy is the most commonly performed surgery in children. Aims: To evaluate the effects of pediatric adenotonsillectomy on health care utilization. Methods: From 2006 to 2017, age/sex-matched adenotonsillectomy participants ( n = 243.396) and controls ( n = 730.188) were selected (62% of male and 38% of female. 47% age≦ 6, 16% 7–9years, 8% 10–12years, 29% 13–18years). The changes in outpatient visits, hospitalization days, and drug prescriptions due to a URI, asthma, and rhinitis before and after the surgery date (from 13 months to 1 month) were compared. Results: Outpatient visits decreased more in the surgery group than the control group (mean change, 3.24 ± 8.61 d and 1.16 ± 6.57 d for URI, 2.07 ± 8.63 d and 0.51 ± 6.47 d for rhinitis, and 0.72 ± 4.81 d and 0.42 ± 3.91 d for asthma, p < .001 for all). Hospitalizations also showed greater decreases in the surgery group (mean change, 0.31 ± 2.96 d and 0.04 ± 1.70 d for URI, 0.13 ± 2.40 d and 0.02 ± 1.48 d for rhinitis, 0.11 ± 2.32 d and 0.04 ± 1.83 d for asthma, p < .001 for all). The prescription of antihistamines, leukotriene modulators, oral antibiotics, oral steroids, and expectorants, cough suppressants and oral bronchodilators was also decreased after surgery. Conclusions: The adenotonsillectomy group showed a greater decrease in post-operative outpatients visits, hospital days and drug prescriptions associated with URI, rhinitis and asthma than the control group.